The Impact of Ground Irregular Sedimentary Structure on the Seismic Motion Amplification Characteristics: A case study in Tottori, Japan - Nagao, Takashi; Ma, Xiao (Engineering, Technology & Applied Science Research, 2023)
The amplification characteristics of seismic motion are determined by the ground structure. In design practice, the ground is assumed to be horizontally stratified. However, the actual ground forms irregular sedimentary structures and the propagation direction of the seismic motion in the soil changes in a complicated way. Thus, the actual amplification factor of seismic motion is dramatically different from the value assumed in design practice. This phenomenon is called the multidimensional effect. The present study targeted at a seismic observation point in Tottori Prefecture, Japan, and estimated the irregular ground structures based on the microtremor observation results. With this ground structure model, Finite Element Analysis (FEA) was conducted and the amplification factors were compared with those determined assuming horizontal stratification. When there is no ground nonlinearity, the multidimensional effect of the ground was more notable in points with thick sedimentary strata, where the peak amplification factor according to the FEA was 1.9 to 3.6 times larger than when horizontal stratification was assumed. In points with thin sedimentary strata, the peak amplification factor ratio was 2.1–2.4. First-order peak frequency was different between cases with irregular ground structures and with horizontal stratification. Furthermore, when the nonlinearity of the ground was evident, the multidimensional effect on the peak amplification factor was not as noticeable as when the ground behaved linearly. The peak magnification ratio due to the multidimensional effect was found to be 2.3. The results of this study show that the amplification characteristics of the seismic motion considered in design practice are likely to be on the dangerous side when the ground is not horizontally stratified.